Epiphytic and epigeal lichens as bioindicators of air pollution in the Burabay National Park, Kazakhstan - ZNANYLKHAN BUKABAYEVA; SARDARBEK ABIYEV; BATIYASH SILYBAYEVA; ULBALA ASSANOVA; ANARGUL SHARIPKHANOVA; BALNUR SAGDATKYZY (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Bukabayeva Z, Abiyev S, Silybayeva B, Assanova U, Sharipkhanova A, Sagdatkyzy B. 2023. Epiphytic and epigeal lichens as bioindicators of air pollution in the Burabay National Park, Kazakhstan. Biodiversitas 24: 2701-2709. Lichens are recognized as a symbiotic association between a fungus (mycobiont) and a chlorophyll-containing partner (photobiont). Because lichens receive all their nutrients from the atmosphere, they are very sensitive to air quality and can be used as bioindicators of pollution by heavy metals, organic compounds and radioactive elements in the air. This study aimed to evaluate the potential of lichens as bioindicators of the heavy metal content in the air in the Burabay National Park, northern Kazakhstan. In the period from 2018 to 2022, we studied the floristic composition of lichens in the national park. To inform air pollution level, we determined the quantitative characteristics and projective cover of an epiphytic lichen Evernia prunastri (L.) Ach. at different heights above ground level, and the heavy-metal content in an epigeal lichen Cladonia alpestris (L.) Rabenh (Syn. Cladonia stellaris (Opiz) Pouzar & V?zda) at different distances from the road edge. We identified 56 species of lichen belonging to 23 genera and 16 families on the roadsides or in the nearby forest. We found that the average number of individuals of E. prunastri decreased as the tree trunk height increased. The largest number of individuals (11.3) was observed at a height of 60 cm, and the smallest (2.5), at a height of 150 cm. The analysis of C. alpestris samples taken at different distances (50, 100, 150, 200 m) from the roadside showed that the concentrations of Pb, Cr, Cd, As, Ga, V, and ?s were high, and for all the elements studied, except for Mn and Be, exceeded Maximum Allowable Concentration. Our study demonstrates that E. prunastri and C. alpestris are sensitive to air pollution from road traffic and can be used as biomonitors of heavy metal pollution in the study area. Because of the ever-increasing anthropogenic pressure on the vegetation of the Burabay National Park, we recommend further research and monitoring of its lichen biota.